Reforming international environmental governance : from institutional limits to innovative solutions - Chambers, W. Bradnee; Green, Jessica F. (United Nations University Press, 2005)
More than 500 international agreements and institutions now influence the governance of environmental problems ranging from climate change to persistent organic pollutants. The establishment of environmental institutions has been largely ad hoc, diffused, and somewhat chaotic because the international community has addressed key environmental challenges as and when they have arisen. The World Summit on Sustainable Development in Johannesburg in 2002 underscored the need to reform the current institutional framework for environmental governance, but failed to come up with any substantive recomm.